Avaliação da ação de desinfetantes e conservantes sobre a viabilidade de Trypanosoma vivax (Ziemann, 1905) e validação da reação de imunofluorescência indireta – RIFI como método de diagnóstico - Andréia Amaral Pinho (2018)
Trypanosoma vivax is a protozoan that causes severe economic damage in cattle. Originating in Africa, where it is transmitted by the tsetse fly, its biological vector, the parasite has adapted to the mechanical transmission and has spread to places where its vector is not present, reaching the Americas. In Brazil, reports of severe outbreaks of T. vivax have occurred in several regions, and in some cases are related to iatrogenic transmission, especially in dairy herds that routinely use intravenous oxytocin. Among the direct diagnostic methods, the Woo technique stands out; however, its accomplishment requires rapid processing of blood. Among the indirect methods, the ELISA and the IFAT are worth highlighting. Due to the economic importance of bovine trypanosomiasis caused by T. vivax, this study aimed to evaluate the action of preservatives as a way to prolong the time of the Woo method; the action of disinfectants on the viability of T. vivax in syringes and needles; the viability of the parasite in oxytocin solutions and to validate IFAT as a diagnostic method. The preservatives analyzed were Proline, Proline+Glucose, Glucose and PSG. The combination of Proline+Glucose was the most efficient preservative, however, its high cost in relation to the benefit verified, does not encourage its use. The addition of oxytocin solution to samples of T. vivax-contaminated blood in 1:1 and 1:200 ratios exerted a negative effect on the viability of the parasite. However, it allowed survival for up to 30 minutes (1:1) therefore, a vehicle capable of transmitting the parasite. The action of sodium hypochlorite (0.5%), alcohol (54°GL) and alkyl dimethyl benzyl ammonium chloride (0.15%) was evaluated in the disinfection of contaminated needles and syringes, through two processes: aspirating/despising the disinfectant or just immersing the syringe/needle in the disinfectant solution for 30 minutes. By the first process all the disinfectants evaluated were efficient in the elimination of T. vivax. Through the immersion process, however, none of the disinfectants was able to completely eliminate the parasite, even though they reduced its viability. In the validation process, the IFAT technique was optimized, to define the most adequate protocol. Its repeatability and reproducibility were evaluated and considered high; the analytical sensitivity was low in relation to the ELISA, however the analytical specificity was total, and there were no cross reactions with other hematozoan evaluated. Regarding the diagnostic characteristics, the technique obtained 82.9% sensitivity and 100% specificity; being adequate for the accomplishment of epidemiological studies of T. vivax infection.